Wpływ hormonalnej terapii zastępczej na wybrane elementy seksualności po histerektomii - Rapa, Dariusz; Paszkowski, Tomasz (Menopause Review/Przegląd Menopauzalny, 2004)
Total abdominal hysterectomy with bilateral salpingo-oophorectomy (TAH&BSO) is one of the most commonly performed operative procedure in gynecology. Non-somatic consequences of this operation relatively rarely have been a subject of scientific analysis. The aim of this study was to assess how selected aspects of sexuality are influenced by hormonal replacement therapy (HRT) after TAH&BSO. Initially 637 women operated in District OB/GYN Departments in Biała Podlaska, Chełm, Lublin and Zamość were included into this study. The included patients were subject to the questionnaire study 1-3 years after TAH&BSO was performed using the same surgical technique (modo Freud) for the non-oncologic indications. An anonymous questionnaire was mailed exclusively to women in whom no intra- and postoperative complications occurred. The final analysis concerned 126 women, who sent back the completed questionnaires, of whom 88 women received HRT after TAH&BSO and the remaining 38 were not subject to any type of hormone substitution. The age of the studied women at the time of operation ranged from 37 to 68 years (median age – 49 years). For the purpose of this study an original questionnaire was created. The results obtained in this study suggest that hormonal replacement therapy after TAH&BSO is associated with positive changes regarding libido and the enrichment of sexual life while it does not change the overall self-evaluation of the quality of sexual life.